Development of an IOT-integrated app for monitoring hydroponic farming systems - Chan, Jia Jun (2024)
As urbanization accelerates in Malaysia, the demand for fresh produce continues to rise, yet the availability of agricultural land is diminishing. Hydroponics, a soil-less cultivation method, presents a viable solution to this challenge. However, managing hydroponic systems can be time-intensive, particularly for urban dwellers with busy lifestyles. This project proposes an IoT-integrated hydroponic farm monitoring mobile application designed to address these challenges. The development of the application focused on a feature-driven approach using React Native, NodeJS, and Flask frameworks. The application enables users to remotely monitor and control environmental parameters within hydroponic farms while receiving real-time notifications about farm status, thereby enhancing overall farm management efficiency. A key aspect of the project was ensuring the application's usability, with features such as environmental parameter trend predictions to facilitate automated hydroponic farm management. This innovation has significant implications for farm management and plant growth, allowing users to manage their time more effectively and increase productivity. Moreover, the application supports plant management by allowing users to record observations and plan tasks with reminder notifications, streamlining the process of tracking plant growth without relying on physical records. Overall, this project contributes to advancing urban agriculture in Malaysia by providing a convenient and efficient mobile solution for managing hydroponic farms, thereby promoting sustainable and efficient urban farming practices.